Editorial: Three Tenets of Environmental Importance. Issue 4 (1st December 2015) - Wilkinson, Nicholas
Abstract : These are Working, Learning and Living. The first and last of Working and Living have been addressed in some of the previous issues of the journal. 'Working' has been supported and developed by books, journals and projects. User decision making processes lie central to these concepts.